Analisis Pengaruh Kompetensi dan Motivasi Intrinsik terhadap Kinerja Karyawan dengan Kepuasan Kerja sebagai Variabel Mediasi (Studi pada Karyawan PT Formosa Bag Indonesia) - Ridho, Fandy Achmad; Widiyanto, Widiyanto (Lembaga Yasin AlSys, 2026)
Improving employee performance is an important issue in manufacturing companies, particularly because of differing findings in previous studies regarding the influence of competence and intrinsic motivation on employee performance. This study aims to analyze the effect of competence and intrinsic motivation on employee performance, with job satisfaction as a mediating variable among employees of PT Formosa Bag Indonesia. This study used a quantitative approach with an explanatory research design. The research sample consisted of 100 employees selected through purposive sampling. Data were collected through questionnaire distribution using a Likert scale and analyzed using the Partial Least Squares (PLS) method. The results show that competence and intrinsic motivation have a positive effect on job satisfaction and employee performance. In addition, job satisfaction was proven to mediate the effect of competence and intrinsic motivation on employee performance. These findings confirm that improving competence and intrinsic motivation can strengthen job satisfaction, which ultimately has an impact on improving employee performance. This study contributes to the development of human resource management studies, particularly regarding the role of job satisfaction as a mediating mechanism in the relationship between competence, intrinsic motivation, and employee performance. The practical implications of this study emphasize the importance of competence development, strengthening intrinsic motivation, and creating a work environment that supports job satisfaction to improve employee performance in manufacturing companies.